Effect of oral premedication with ivabradine on surgical field and intraoperative bleeding during functional endoscopic sinus surgeries: A prospective, randomized, and placebo-controlled study - Sowmya Madihalli Janardhan Iyengar; Surekha Kumar; Shankar Kantharaju (Asian Journal of Medical Sciences, 2023)
Background: Ivabradine is an effective drug to prevent abnormal increase in heart rate (HR). Aims and Objectives: The aims of this study were to determine if a pre-operative oral dose of ivabradine (2.5 mg) reduces intraoperative bleeding during functional endoscopic sinus surgery (FESS) and improves visualization of operative field. Materials and Methods: A prospective, randomized, and placebo-controlled study was carried out in 30 patients of ASA grade I and II, aged between 18 and 60 years undergoing FESS surgeries. The patients were randomly allocated into two groups. Group I – received 2.5 mg of tablet ivabradine and Group P – received a placebo (vitamin tablet) 1 h before surgery. Blood loss and hemodynamic parameters (HR, systolic, diastolic, and mean blood pressure) were assessed perioperatively. Surgical field was graded by operating surgeon using Fromme – Boezaart score (FBS) at the end of procedure. Post-operative monitoring for any complications was also done. Results: Mean final blood loss in Group I was 165.73±43.48 mL and in Group P was 246.25±30.76 mL. There was a significant difference in mean final blood loss (mL) between two groups with P<0.001. In Group I – 13.33% had FBS 1 and 86.67% had FBS 2, whereas in Group P – 6.67% had FBS 2, 86.67% had FBS 3, and 6.67% had FBS 4. Thus, Group I had lower FBS scores than Group P and was statistically significant. Conclusion: Pre-operative oral ivabradine helps in reducing intraoperative bleeding in FESS surgery and provides good surgical field compared to placebo.